Edukasi dan Konseling Berbasis Gender dalam Pencegahan Kekerasan Seksual pada Remaja - Tindaon, Rotua Lenawati; Lisa, Mona; Afandy, Muhamad Ridwan (FORIKES, 2025)
Sexual violence against adolescents is a serious problem that requires gender-based education and counseling interventions in schools. The purpose of this study was to analyze the effectiveness of gender-based education and counseling in improving adolescents' knowledge and attitudes regarding sexual violence prevention. The study used a one-group pre-test–post-test design with 50 proportionally selected female students in grades X–XII. Knowledge and attitude variables were measured using a structured questionnaire that had been tested for validity and reliability. Data were analyzed descriptively and using the Wilcoxon test. The results showed an increase in the mean knowledge score from 70 to 80 and in the attitude score from 62.5 to 74 after the implementation of gender-based education and counseling. The Wilcoxon test showed a significant difference between the knowledge scores before and after the intervention (p = 0.001) and between the attitude scores before and after the intervention (p <0.001). This difference aligns with the increase in the mean score, indicating a positive direction of change. It can be concluded that gender-based education and counseling successfully improved adolescents' knowledge and attitudes regarding sexual violence prevention, and therefore deserves to be recommended as a school-based sexual violence prevention strategy.Keywords: sexual violence; teenagers; education; knowledge; attitude ABSTRAK Kekerasan seksual pada remaja merupakan masalah serius yang menuntut adanya intervensi edukasi dan konseling berbasis gender di lingkungan sekolah. Tujuan penelitian ini adalah menganalisis efektivitas edukasi dan konseling berbasis gender dalam meningkatkan pengetahuan dan sikap remaja tentang pencegahan kekerasan seksual. Penelitian menggunakan desain one-group pre-test–post-test pada 50 siswi kelas X–XII yang dipilih secara proporsional. Variabel pengetahuan dan sikap diukur menggunakan kuesioner terstruktur yang telah diuji validitas dan reliabilitasnya. Data dianalisis secara deskriptif dan dengan uji Wilcoxon. Hasil penelitian ini menunjukkan adanya peningkatan skor rerata pengetahuan dari 70 menjadi 80 dan sikap dari 62,5 menjadi 74 setelah pelaksanaan edukasi dan konseling berbasis gender. Uji Wilcoxon menunjukkan bahwa terdapat perbedaan yang bermakna antara skor pengetahuan sebelum dan sesudah intervensi (p = 0,001) serta antara skor sikap sebelum dan sesudah intervensi (p <0,001). Perbedaan ini sejalan dengan peningkatan skor rerata sehingga menunjukkan arah perubahan yang positif. Dapat disimpulkan bahwa edukasi dan konseling berbasis gender berhasil meningkatkan pengetahuan dan sikap remaja tentang pencegahan kekerasan seksual, sehingga layak direkomendasikan sebagai salah satu strategi pencegahan kekerasan seksual berbasis sekolah.Kata kunci: kekerasan seksual; remaja; edukasi; pengetahuan; sikap